Knowledge of Saudi Population about Parkinson Disease - Fouly, Raghad Taha; Sahli, Angham Ali; Alqahtani, Bashaier Gubran; Algosair, Ibrahim Saleh; Garbo, Mosaed Saif Al; Rayyani, Sarah Ahmed (International Journal of Innovative Research in Medical Science, 2020)
Background: Parkinson Disease is the second most common degenerative neurological disease, with Alzheimer’s disease being the first. Considering the increasing prevalence of PD and the need for early detection by increasing community awareness of the symptoms to delay the serious complications and improving quality of life. Due to the lack of researches about community awareness, this study aimed to measure the level of knowledge of Saudi community about the symptoms of Parkinson disease. Aim: To measure the level of public knowledge of the symptoms of Parkinson disease in Saudi population. Methods: This is a questionnaire-based cross-sectional study. It will be carry out among male and female population older than 18 years in Kingdom of Saudi Arabia, KSA. The Samples selected randomly via electronic questionnaire during the period from April 2018 to September 2018. Descriptive analysis done by using Statistical Package for Social Sciences (SPSS). An exploratory cross-sectional design, using both quantitative and qualitative methods used in this study. The questionnaire divided into two sections, the first section will concern with information of the participants. However, the second section will examine the personal knowledge about symptoms of Parkinson's disease. Results: We found that the total awareness was high which indicate that the population had an awareness better than we thought. Conclusion: the knowledge of PD motor symptoms among Saudi population found to be higher than expected. More researches targeting other aspects of Parkinson disease and specific subgroups are necessary to improve public awareness and knowledge about PD.